Photoluminescence properties and efficient energy transfer of Ce3+/Eu2+ activated K2Ba7Si16O40 phosphors. (May 2018) - Wang, Wanrong; Yang, Yuanqing; Liu, Yali; Pan, Dai; Luo, Xu; Yan, Shan; Xiang, Guotao; Jin, Ye
Graphical abstract: Ce 3+ /Eu 2+ doped K2 Ba7 Si16 O40 phosphors have been synthesized and resonance-type energy transfer from Ce 3+ to Eu 2+ has been demonstrated. Highlights: K2 Ba7 Si16 O40 :Ce 3+ /Eu 2+ phosphors have been synthesized by a high temperature solid-state method with CO atmosphere. The resonance-type energy transfer by dipole-dipole interaction from Ce 3+ to Eu 2+ in K2 Ba7 Si16 O40 is demonstrated. The critical distance between Ce 3+ and Eu 2+ ions is calculated to be 25.06 Å. The thermal activation energy of K2 Ba7 Si16 O40 is calculated to be 0.26 eV. Abstract: Ce 3+ /Eu 2+ activated K2 Ba7 Si16 O40 phosphors have been synthesized via a high-temperature solid-state method with CO atmosphere. Under ultraviolet (UV) light pump, the photoluminescence (PL) spectra of K2 Ba7 Si16 O40 : Ce 3+ is composed of a broadband from 300 nm to 500 nm ascribed to the spin-allowed 5d–4f transition of Ce 3+ ions. The optimal concentration is 8% for Ce 3+ single doped K2 Ba7 Si16 O40 due to the ernergy dispersion between Ce 3+ ions and the critical distance between Ce 3+ ions is 15.05 Å. K2 Ba7 Si16 O40 : Eu 2+ emits a broad green emission peaking at 498 nm. The spectral overlap between the emission of Ce 3+ and the excitation of Eu 2+ suggests the resonance-type energy transfer from Ce 3+ to Eu 2+, which is further demonstrated by the decay curves of K2 Ba7 Si16 O40 : 8 mol% Ce 3+, m Eu 2+ . The critical distance between Ce 3+ and Eu 2+ ions is calculated to be 25.06 Å by Dexter's theory. Furthermore, the energy transfer mechanism is dipole-dipole interaction. In addition, the thermal activation energy is calculated to be 0.26 eV. The CIE coordinates can be tuned from blue to green by increasing Eu 2+ ions. All results suggest that K2 Ba7 Si16 O40 : Ce 3+, Eu 2+ is potentially useful for near-UV pumped white LEDs.